Peran Teks Eksposisi dalam Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas 5 SD - Mutia Casadilla; Chandra Chandra; Salmaini Safitri Syam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study investigates the role of expository texts in enhancing critical thinking skills among fifth-grade elementary school students through a qualitative approach. Data were collected by conducting interviews with five fifth-grade students to explore their experiences and perceptions related to reading expository texts. The findings reveal that engaging with expository texts helps students develop reasoning abilities, stimulates curiosity, and supports the formation of argumentation skills. Students expressed that such texts encouraged them to think more deeply and analyze information logically. The study underscores the importance of integrating age-appropriate expository materials into classroom instruction to foster higher-order thinking. It also highlights the need for teaching strategies that actively engage young learners in reflective and analytical thought processes.